1998
DOI: 10.1002/(sici)1521-3773(19980817)37:15<2136::aid-anie2136>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Reduction of Diphenylacetylene by Metallic Lithium

Abstract: A zero-order reaction converts cis-dilithiostilbene (1), formed upon reduction of diphenylacetylene by lithium, into the trans isomer 2. The cis-monolithiated adduct acts as a catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Additionally, the acenaphthylene 237 was also reduced by lithium in the presence of 4,4'-di-tert-butylbiphenyl (DTBB) producing the corresponding dianion, which was subsequently treated with different carbonylic compounds yielding the expected trans-1,2-disubstituted derivatives 238 (Scheme 62) [147]. The mechanism of the reduction of diphenylacetylene with lithium was discussed, showing that (Z)-1,2-dilithio-1,2-diphenylethene was formed as the most stable isomer, what is in sharp contrast with the trans preference for aliphatic dilithioethenes [148]. Maercker and co-workers described the preparation of the 3,4-dilithio-2,5-dimethylhexa-2,4-diene 240 by reduction of the 2,5-dimethylhexa-2,3,4-triene 239 with lithium metal, and the subsequent reaction with different electrophiles [149].…”
Section: Other Methodsmentioning
confidence: 99%
“…Additionally, the acenaphthylene 237 was also reduced by lithium in the presence of 4,4'-di-tert-butylbiphenyl (DTBB) producing the corresponding dianion, which was subsequently treated with different carbonylic compounds yielding the expected trans-1,2-disubstituted derivatives 238 (Scheme 62) [147]. The mechanism of the reduction of diphenylacetylene with lithium was discussed, showing that (Z)-1,2-dilithio-1,2-diphenylethene was formed as the most stable isomer, what is in sharp contrast with the trans preference for aliphatic dilithioethenes [148]. Maercker and co-workers described the preparation of the 3,4-dilithio-2,5-dimethylhexa-2,4-diene 240 by reduction of the 2,5-dimethylhexa-2,3,4-triene 239 with lithium metal, and the subsequent reaction with different electrophiles [149].…”
Section: Other Methodsmentioning
confidence: 99%
“…However, these compounds are not reactive enough for promoting reactions as Lewis acid catalysts. For this reason, and in order to improve the acidity of these bimetallic compounds, the bis-trimethylstannyl derivative 111 (R3M = Me3Sn) was treated with 6 equivalents of SnCl4 to give (R)-2,2'-bis(dichloromethylstannyl)-1,1'-binaphthyl (112), which shows promising catalytic properties and can be considered as the first chiral bis-metallic binaphthyl catalyst (Scheme 27) [61]. Clayden and co-workers reported recently a resolution of racemic 2,2'-dilithio-1,1'-binaphthyl (110) by reacting it with (-)-menthyl p-methylbenzene sulfinate, giving a mixture of two atropodiastereoisomeric sulfoxides, which can be separated by chromatography or crystallization [62].…”
Section: Scheme 21mentioning
confidence: 98%
“…The addition of MeOH at the same temperature yielded pure cis-stilbene as the only product (235; X = H), whereas cis-PhCD=CDPh (235; X = D) is formed on addition of MeOD. Since the reduction takes place on the surface of the metal, the addition of a second lithium atom is favored over any other outcome to give the dilithium aduct 234 (Scheme 53) [112].…”
Section: Dilithium Compounds By Reductive Lithiation Of Unsaturated Cmentioning
confidence: 99%
“…Diphenylacetylene can be reduced by metallic lithium to form the cis-dilithium adduct 7, which was converted into cis-stilbene after treatment with methanol [11]. It has been found that trimethylsilyl substituted styrenes can also be reduced by metallic lithium to form the corresponding 1,2-dilithio intermediate 8 (Scheme 4) [12].…”
Section: 2-bimetallic Compoundsmentioning
confidence: 99%